Multiple perspectives on engaging future engineers - Wilson, Denise Michelle; Adams, Robin S.; Evangelou, Demetra; English, Lyn; De Figueiredo, António Dias; Mousoulides, Nicholas; Pawley, Alice L.; Schifellite, Carmen; Stevens, Reed R.; Svinicki, Marilla D.; Trenor, Julie Martin (My University, 2011)
BACKGROUND: Engaging future engineers is a central topic in everyday conversations on engineering education. Considerable investments have been made to make engineering more engaging, recruit and retain aspiring engineers, and to design an education to prepare future engineers. However, the impact of these efforts has been less than intended. It is imperative that the community reflects on progress and sets a more effective path for the future. PURPOSE: The purpose of this article is to map a new innovation landscape for what it means to engage future engineers. This is a theoretically grounded divergent-thinking effort to enable a broader space of high impact innovations for engaging future engineers. SCOPE/METHOD: A multiple perspectives methodology drawing from innovation, cross-disciplinary, and boundary work frameworks was used to make visible multiple facets of engaging future engineers. Scholars from diverse communities of thought and discourse were selected to present interparadigmatic perspectives, act as boundary agents, challenge and transform current ways of thinking, and illustrate new opportunities for engineering education innovation. CONCLUSIONS: A new innovation landscape for engaging future engineers is needed, one that emphasizes epistemological development and social justice, new configurations on engineering thinking and connecting to the formative years of development, the entwinement of engineering knowing and being, and mutually informing consequences for opening up a broader space for innovation.We also need to adopt strategies and tools for using a multiple perspectives approach to better understand complex engineering education problems. 2011 ASEE.
Keywords: Epistemological development; Multiple perspectives; Complexity